From the Puppet Screen to the Accounting World: Integrating Semar’s Philosophy and Islamic Spirituality in the Profession of Accountant Educators - Felisia Evieta Yakin; Ardins Kristiani Selfhana Hendrik (Universitas KH. Abdul Chalim Mojokerto, 2025)
The teaching accountant profession plays an important role in the world of education, so the demand to understand a curriculum based on spirituality will always accompany this profession. This research aims to analyze the philosophy of Semar and Islamic spirituality in the teaching accountant profession. The method used in this research is a literature study. The data sources used are scientific articles, books, news, and other relevant sources. Data collection techniques through review of all previously collected data. The data was analyzed qualitatively. The results of this study conclude that Semar is a character with various unique characteristics. His character can be used as a role model in living life, such as religious, intelligent, wise, and oriented to the public interest. On the other hand, the aspect of spirituality also has an important role in supporting the understanding of the morals and ethics of educator accountants based on the teachings of the Qur'an and hadith that lead to goodness.